Quantificação do colágeno, da composição centesimal e estudo dobalanço de massa dos nutrientes declarados, na avaliação da qualidade de salsichas - Ana Paula Ribeiro Angelini (2011)
Seven commercial brands of Brazilian sausages purchased in the citiesof Belo Horizonte/MG and Porto Alegre/RS were evaluated according to quality laws in Brazil, Europe and North America. Through the analysis of chemical composition and estimated formulation, calculated using the proposed methodology, it was observed that 71.43% of the commercial brands showed nonconformity to Normative Instruction No. 4 and/or RDC No. 360. The levels of collagen and connective tissue were determined and presented according to the limits of international law adopted, it because these quality parameters are not included in the Brazilian legislation.